Epidemiologia e organização de serviços de saúde: Diabetes Mellitus numa comunidade de Porto Alegre - Mielczarski, Rodrigo Geisler (Universidade do Vale do Rio do Sinos, 2008)
This study aimed to assess service condition process and results for people aged over 20 years, diagnosed with diabetes mellitus and living in an area covered by the Unidade Básica de Saúde Vila Gaúcha (Vila Gaúcha Basic Health Unit), in the city of Porto Alegre. Disease control rate of interviewees with self-reported diabetes was assessed. Definition of this rate was established from arterial pressure values, glycosylated hemoglobin, abdominal circumference, and/or BMI. Of the 752 people aged over 20 years, 37 (4.9%; 95% CI 3.4 – 6.5) mentioned diabetes mellitus diagnosed by a doctor. Disease control rate measurements could be performed in 31 (83.8%) people. Results revealed 24 (77.4%) individuals with altered blood pressure levels, 25 (80.6%) with BMI equal to or above 25 kg/m², 29 (93.5%) with abdominal circumference above normal and 18 (58.1%) with glycosylated hemoglobin equal to or above 8%. In terms of result indicators, diagrams were used to analyze disease control rate factors. Only one patient was c
Keywords: atenção primária à saúde; avaliação de processos e resultados; estudos transversais; qualidade dos cuidados de saúde; Diabetes Mellitus; cross-sectional studies; outcome and process assessment; primary health care; quality of health care; Ciências da Saúde